Resistance training alleviates muscle atrophy and muscle dysfunction by reducing inflammation and regulating compromised autophagy in aged skeletal muscle - Cao, Yangfan; Zhou, Jiawei; Quan, Helong; Li, Wei; Li, Ting; Wang, Lifeng (Frontiers in Immunology, 2025)
BackgroundAge related muscle atrophy is associated with chronic inflammation and impaired autophagy. Resistance training serves as an effective intervention for enhancing skeletal muscle hypertrophy.MethodsThis study utilized a naturally aged mouse model to investigate the role of the mammalian target of rapamycin complex 1 (mTORC1) pathway in mediating the effects of resistance training on chronic inflammation and autophagy in aged skeletal muscle.ResultsOur findings demonstrate that resistance training increased the wet weight of the gastrocnemius (GAS) and quadriceps (Quad), absolute number of fibers and the cross-sectional areas (CSA) of skeletal muscles, as well as enhanced the maximum load and maximum grip strength. These findings indicate that resistance training improved the quality and strength of skeletal muscles in aging mice. Resistance training alleviated inflammation in aged skeletal muscle by promoting M2 macrophage polarization, reducing the mRNA levels of tumor necrosis factor alpha (TNF-α), nuclear factor-kappaB (NF-κB) and interleukin-1beta (IL-1β), and increasing the mRNA levels of interleukin-6 (IL-6) and interleukin-10 (IL-10). In aged skeletal muscle, resistance training decreased the protein expression of mTOR, regulatory-associated protein of mTOR (Raptor), p70 ribosomal protein s6 kinase (p70S6K), IL-1β, and hypoxia-inducible factor 1-alpha (HIF-1α) without affecting protein kinase B (AKT) activity. Moreover, autophagy, which is reduced in aged muscle, was increased by resistance training through increased AMP-activated protein kinase (AMPK) activity and increased BCL-2-interacting protein 1 (Beclin1) and transcriptional factor EB (TFEB) expression.DiscussionOur study suggests that resistance training was associated with alleviated inflammation and regulated autophagy, potentially involving the mTORC1-HIF-1α and mTORC1-AMPK pathways, which may contribute to improved skeletal muscle mass in aged mice.